Cogent: a coherence-driven cognitive agent modelling and experimentation framework. (2019) - Sivaraj, Sunit; Yilmaz, Levent
Most agent modelling and simulation languages lack high-level syntactic features necessary for cognitive modelling. In this paper, we present Cogent, an interactive coherence-driven agent specification and simulation platform and demonstrate its use in ethical decision making. The underlying strategy is based on the concept of a connectionist, interactive activation model that implements the theory of coherence. Agents in the Cogent language are specified by a domain-specific language (DSL). The DSL provides the syntax for specifying the decision-making strategy along with its cognitive coherence model. The framework also provides the ability to model complex hierarchical cognitive network structures. To illustrate the utility of Cogent, we explore a machine ethics case study.